2019
DOI: 10.1016/j.advwatres.2019.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Flood inundation modeling in urbanized areas: A mesh-independent porosity approach with anisotropic friction

Abstract: In the present work, a porosity-based numerical scheme for the Shallow Water Equations is presented. With the aim of accounting for the presence of storage areas, such as gardens, yards and dead zones, and for preferential flow pathways, both an isotropic storage porosity parameter and anisotropic friction are adopted. Particularly, the anisotropic effects due to the building alignments are evaluated defining conveyance porosities along principal directions and using them to express the friction losses in tens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 51 publications
1
35
0
Order By: Relevance
“…In general, the most important results for quantifying the hazard for human lives are the maximum simultaneous water depth and velocity, which 10 can be represented in terms of Froude number, total head, total force and/or total depth. This last indicator, which represents the water depth at rest D whose static force is equivalent to the total force of the flow, is evaluated as follows (Aureli et al, 2008b;Ferrari at al., 2019):…”
Section: Results 15mentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the most important results for quantifying the hazard for human lives are the maximum simultaneous water depth and velocity, which 10 can be represented in terms of Froude number, total head, total force and/or total depth. This last indicator, which represents the water depth at rest D whose static force is equivalent to the total force of the flow, is evaluated as follows (Aureli et al, 2008b;Ferrari at al., 2019):…”
Section: Results 15mentioning
confidence: 99%
“…CC BY 4.0 License. performance of this code for field applications was assessed in previous works (Vacondio et al, 2016;Dazzi et al, 2018Dazzi et al, , 2019Ferrari et al, 2018Ferrari et al, , 2019.…”
Section: The Parflood Modelmentioning
confidence: 99%
“…In the last decades, great attention has been paid to the development of numerical solvers for the SWE (Toro and Garcia-Navarro, 2007;Toro, 2009). The latter tackle directly the SWE by means of the finite volumes discretization and have reached a sufficient level of complexity so that they are able to account for crucial issues such as to cite just a few, the treatment of topography source terms (Duran and Marche, 2014;Hou et al, 2018), the use of unstructured grids (Zhao et al, 2019), and the evolution of wet-dry fronts (Ferrari et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Fixed obstacles and transportable floating bodies were compared by Albano et al [7] to analyze the mitigation efficiency of different structural interventions. In addition, porosity has been adopted as a statistical descriptor and introduced into classic shallow water equations (SWEs) to reflect the impact of buildings on urban flooding [8][9][10][11]. Wu et al indicated that increasing bed elevation is still a common method to represent the blockage effect of buildings on surface flow [12].…”
Section: Introductionmentioning
confidence: 99%
“…An et al used the Gerris open source code for SWEs to validate model performance when embedded solid boundaries were included [16]. Ferrari et al compared isotropic and anisotropic schemes using the Toce case and found that the latter showed better agreement with the measurements than the former [8]. Costabile analyzed the Toce case in terms of model suitability for representing the influence of obstacles on flow propagation [17].…”
Section: Introductionmentioning
confidence: 99%